PELAKSANAAN PROMOSI OBJEK WISATA TAMAN REKREASI STANUM BANGKINANG KABUPATEN KAMPAR - Saputri, Indry Kurnia; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Promotion is way of communicating used by companies or organizations toencourage or attract potential customers to buy products or services marketed. Thepurpose of this study is to determine the implementation of promotion of attractionsstanum bangkinang and obstacles in the implementation of promotions. The researchuse qualitative method with descriptive approach, research subject is managerial taskforce team as manager, staff of administration park stanum, employee in charge ofguarding indopura stanum pool. Data collection conducted in this by interview,observation and documentation. The result of this research is promotion of stanumbangkinang recreation park doing promotion through two media or promotion mixthat is advertising, and public relation, but the result is not good. Obstacles faced inthe implementation of promotions through the two media promotion mix is in terms orthe market (kinds of buyers are diverse) funds for limited promotion, still in the stageof remodeling and renovation so it has not focused on promotion.Keywords: promotion tour, promotional mix, recreation par